2007
DOI: 10.1111/j.1526-4610.2007.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vertigo, Dizziness, and Migrainous Vertigo in Patients With Migraine

Abstract: Objective.-The aim of this study was to determine the lifetime prevalence of vertigo and dizziness in patients with migraine as compared with controls and to establish the lifetime prevalence of migrainous vertigo.Background.-Dizziness and vertigo are relatively frequent complaints in general population; however, the prevalence of migrainous vertigo has not been extensively studied so far.Methods.-The study included 327 migraine patients and 324 controls who do not suffer from frequent headaches. The study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 40 publications
4
108
0
2
Order By: Relevance
“…Vertigo is two to three times more common in patients with migraine than in headache-free controls [ 33,59 ] and in patients with tension-type headaches [ 31 ]. Vice versa, the prevalence of migraine has been shown to be elevated among patients with unclassified or idiopathic vertigo [ 2,34,54 ].…”
Section: Epidemiological Association Of Migraine and Vertigomentioning
confidence: 99%
“…Vertigo is two to three times more common in patients with migraine than in headache-free controls [ 33,59 ] and in patients with tension-type headaches [ 31 ]. Vice versa, the prevalence of migraine has been shown to be elevated among patients with unclassified or idiopathic vertigo [ 2,34,54 ].…”
Section: Epidemiological Association Of Migraine and Vertigomentioning
confidence: 99%
“…Brantberg et al [11] found that only half the MRV patients have never had a headache simultaneously with their vertigo attacks. Vuković et al [7] reported that in one group of migraine patients who experienced vertigo in their lifetime, vertigo symptoms coincided with the migraine attack in only 23.2% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are different epidemiologic studies which confirmed this relationship [1][2][3][4][5][6][7], and in the last few years, many authors have published studies which throw fresh light on a new concept of migraine as a cause of various forms of vestibular dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms vary for each individual, and the duration and frequency of vestibular symptoms may change over time [12]. In a 2007 retrospective review, Vuković et al [13] compared the prevalence of dizziness among those with and without migraines. The authors reported that 51.7% of 327 migraine patients experienced vertigo in their lifetime compared with 31.5% of 324 people in the control group.…”
Section: Clinical Presentationmentioning
confidence: 99%